Wage Compression within the Firm: Evidence from an Indexation Scheme. Issue 624 (29th May 2019) - Leonardi, Marco; Pellizzari, Michele; Tabasso, Domenico
Abstract: We revisit the role of labour market institutions by showing how they affect the sharing of firm-specific rents between employers and employees. We look at an Italian wage indexation mechanism ('Scala Mobile') that compressed the distribution of wages, imposing real wage increases at the bottom of the distribution. After developing a simplified version of a search model with intra-firm bargaining and on-the-job search, we document that skilled workers received lower wage adjustments when employed at firms with many unskilled workers and they tended to move towards more skill-intensive firms. Moreover, the system drove the least skill-intensive firms out of the market.